2019
DOI: 10.1016/j.ijscr.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal tubular papillary neoplasm (ITPN), a novel entity of pancreatic epithelial neoplasms and precursor of cancer: A case report and review of the literature

Abstract: HighlightsIntraductal tubular papillary neoplasm (ITPN) displays a very rare subtype of epithelial neoplasms of the pancreas.To date, little is known about ITPN and particularly about pancreatic cancer arising in this tumor entity.ITPN reveals a potential of malignant transformation. Radical surgical resection and oncologic follow-up is warranted.When compared to ductal adenocarcinoma, patients with ITPN reveal less lymph node metastasis and a better overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…A literature review of 30 case reports had analyzed the prognosis in 20 of the studies and reported average survival time to be 28.6 months post-diagnosis, with most cases having no evidence of remaining disease after resection and treatment [ 5 ]. A particular case report in which a patient with ITPN and no metastases underwent pylorus-preserving duodenopancreatectomy showed survival at five months post-surgery with no evidence of remaining disease [ 9 ]. However, the prognosis of ITPN is favorable in comparison to the more commonly encountered pancreatic ductal adenocarcinomas, where median disease-specific survival was 17.0 months in a dataset of 4383 patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of 30 case reports had analyzed the prognosis in 20 of the studies and reported average survival time to be 28.6 months post-diagnosis, with most cases having no evidence of remaining disease after resection and treatment [ 5 ]. A particular case report in which a patient with ITPN and no metastases underwent pylorus-preserving duodenopancreatectomy showed survival at five months post-surgery with no evidence of remaining disease [ 9 ]. However, the prognosis of ITPN is favorable in comparison to the more commonly encountered pancreatic ductal adenocarcinomas, where median disease-specific survival was 17.0 months in a dataset of 4383 patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITPN is considered a precursor lesion to invasive pancreatic ductal adenocarcinoma [ 4 , 11 , 21 23 ]. Approximately 40% to 50% of ITPN cases harbor an invasive component and they should be referred to as cases of “ITPN with an associated invasive carcinoma” [ 2 , 7 , 10 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% to 50% of ITPN cases harbor an invasive component and they should be referred to as cases of “ITPN with an associated invasive carcinoma” [ 2 , 7 , 10 , 22 ]. Male sex, large tumor size, dilated pancreatic duct with pancreatoliths and high Ki-67 labelling index could be considered as predictive factors for invasiveness [ 2 , 23 ]. Rare cases of patients with lymphovascular and perineural invasion, lymph node and liver metastases are reported in literature [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations